Effects of castration on contraction and α(1)-adrenoceptor expression in rat prostate - Homma, Yukio (2000)
1. The prostate function is regulated by androgens and α-adrenergic activity. Clinically, antiandrogens and/or α(1)-adrenergic antagonists are commonly used to treat symptomatic prostatic hypertrophy. To elucidate the effects of androgen deprivation on prostate contractility via α(1)-adrenoceptor, the characteristics and expression of α(1)-adrenoceptors were examined in castrated rats. 2. Isolated prostate strips from intact and castrated rats were subjected to a phenylephrine stimulated contraction. Prazosin (10 nM), [(3)H]-prazosin and phenoxybenzamine (3–300 nM) were used for inhibition assay, receptor characterization and partial alkylation of α-adrenoceptor, respectively. The mRNA content of three subtypes of α-adrenoceptors was determined by reverse transcription combined with polymerase chain reaction (RT–PCR). 3. Contractile response to phenylephrine increased in castrated rats, which could be explained by a relative increase of the stromal component. A lowered contraction potency was also noted in castrated rats. Receptor binding assay indicated minimal changes in the affinity or density of α(1)-adrenoceptor. Escalating alkylation of the α(1)-adrenoceptor population resulted in a rightward shift in the contraction-response curves before depressing maximal contractile force, and the suppression was detected at lower doses in castrated rats. RT–PCR study confirmed the expression of three types of α(1)-adrenoceptor, α(1a), α(1b) and α(1d)-adrenoceptors, in intact rat prostate, and revealed that α(1a)-adrenoceptor, but not α(1b) or α(1d)-adrenoceptors, was down-regulated in castrates. 4. The results show that androgen deprivation suppressed α(1)-adrenergic contractility of rat prostate strips, and the suppression was associated with down-regulation of receptor reserve for the α(1a)-adreneroceptor population expressed in intact rat prostate.